Si/SiO2 Core/Shell Luminescent Silicon Nanocrystals and Porous Silicon Powders With High Quantum Yield, Long Lifetime, and Good Stability - Gelloz, Bernard; Juangsa, Firman Bagja; Nozaki, Tomohiro; Asaka, Koji; Koshida, Nobuyoshi; Jin, Lianhua (Frontiers in Physics, 2019)
Most of the highly efficient luminescent silicon nanocrystals (SiNCs) reported to date consist of organically capped silicon cores. Here, we report a method of obtaining Si/SiO2 core/shell nanoparticles emitting at a peak energy of 1.5 eV with very high quantum yields (53–61%). The same method led to quantum yields of 30% for porous silicon powder emitting at 1.9 eV. The SiNCs were very stable under continuous excitation for several hours. The lifetime at 1.5 eV was over 232 μs, the longest ever reported for SiNCs, consistent with the very high luminescence efficiency. The SiNCs were first fabricated by non-thermal plasma synthesis or anodization in the case of porous silicon. Then, a thin oxide shell ( 1 nm) was grown using high-pressure water vapor annealing. This oxidation process allows for the growth of very good quality oxide with low defect concentration and low stress, resulting in very good surface passivation, which explains the very high quantum yields obtained.